Process Optimization Of EDM Cutting Process On Tool Steel Using Zinc Coated Electrode - Hashim, Hanizam; Mohamad, Noraiham; Azlan, Umar Al-Amani; Mohd Ahyan, Muhammad Qamaruddin (EDP Sciences, 2017)

(untitled)
In WEDM machining process, surface finish quality depends on intensity and duration of spark plasma. Electrode wire diameter has significant effect on the spark intensity and yet the studies on this matter still less. Therefore, the main objectives of this studies are to compare the different diameters of zinc coated and uncoated brass electrode on H13 tool steel surface roughness. The experiments were conducted on Sodick VZ300L WEDM and work piece material of tool steel AISI H13 block. Electrode of zinc coated brass with diameters of 0.1 mm, 0.2 mm, 0.25 mm and uncoated brass 0.2 mm were used. The surface roughness of cutting was measured using the SUR-FTEST SJ-410 Mitutoyo, surface roughness tester. The results suggest that better surface roughness quality can be achieved through smaller electrode wire diameter. The zinc coated improves flushing ability and sparks intensity resulting in better surface finish of H13 tool steel. New alloys and coating materials shall be experimented to optimized the process further.